I have a question I have come across in an old exam paper which I am trying to work through.
It states that a formal proof must be given using the rules of natural deduction
Now generally what I do is I work backwards to see how I could derive the conclusion then I start working forward.
Two problems I am having:
1) For C → D ∨ E this does not look well formed to me as it is lacking parentheses so it seems ambiguous to me. I have chosen to rewrite this as follows (C → D) ∨ E.
2) Working backward initially I use conditional introduction in my sub-proof before my conclusion.
See below:
I have chosen to reiterate B line 7 as I want to be able to derive by elsewhere in my proof.
I am not sure how to proceed next. I thought of perhaps using contradiction elimination by finally deriving a contradiction and ultimately asserting C → D.
Some advice on how to proceed would be greatly appreciated.
Thanks
The usual convention for the omission of parentheses is that :
1) the negation symbol applies to as little as possible
2) $\land$ and $\lor$ apply to as little as possible, given the above convention.
Thus, $C \to D \lor E$ must be :